The placenta : from development to disease - Kay, Helen H.; Nelson, D. Michael; Wang, Yuping, MD. (Chichester, West Sussex : Wiley-Blackwell, 2011)
The Placenta: From Development to Disease examines research into placental function and its clinical implications to provide a springboard for improving clinical practice and enhancing medical research. Influential information is extracted from the compelling narrative by the use of 'take home' features including: Clinical Pearls - point to important issues in clinical practiceResearch Spotlights - highlight key insights into placental understandingTeaching Points - explain basic concepts for novice readersThe Placenta: From Development to Disease is ideal for both experienced clinicians and r.
Front Matter -- Fetal Origins of Adult Disease/Programming. Maternal Undernutrition and Fetal Programming: Role of the Placenta / Louiza Belkacemi, D Michael Nelson, Mina Desai, Michael G Ross -- Cardiovascular Health and Maternal Placental Syndromes / Shahzya S Huda, Ian A Greer -- Placental Development, Physiology, and Immunology. Development and Anatomy of the Human Placenta / Roxane Rampersad, Mila Cervar-Zivkovic, D Michael Nelson -- Immunologic Aspects of Pregnancy / Joan S Hunt, Margaret G Petroff -- Vascular Development in the Placenta / Berthold Huppertz -- Hypoxia and the Placenta / Stacy Zamudio -- Placental Metabolism / Nicholas P Illsley -- Placental Hormones: Physiology, Disease, and Prenatal Diagnosis / Jennifer M McNamara, Helen H Kay -- Placental Transfer in Health and Disease / Caroline Wright, Colin P Sibley -- Placental Fat Trafficking / Christina Scifres, Yoel Sadovsky -- Maternal-Fetal Cell Trafficking and Microchimerism / Hilary S Gammill, Suzanne E Peterson, J Lee Nelson -- Imprinting in the Human Placenta / Shu Wen, Ignatia B Van den Veyver -- Placental Membranes and Amniotic Fluid Retention / Marie H Beall, Michael G Ross -- Examination of the Placenta, Membranes, and Cord. Examination of the Placenta, Membranes and Cord: Basic Examination / Frederick T Kraus -- The Umbilical Cord / Raymond W Redline -- Ultrasound Imaging and Doppler Studies of the Placenta / Methodius G Tuuli, Anthony O Odibo -- Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET) of the Placenta / Christine H Comstock, Helen H Kay -- Chorionic Villus Sampling and Amniocentesis / Marion S Verp -- Cordocentesis and Fetoscopy / Cristiano Jodicke, Ray Bahado-Singh -- Research Techniques to Study the Placenta. Trophoblast Isolation and Culture / Mila Cervar-Zivkovic, Christina Stern -- Isolation and Culture of Human Umbilical Vein Endothelial Cells / Yuping Wang -- Perfusion Technique for Studying the Placenta Cotyledon / Leslie Myatt -- Three-Dimensional Culture Modeling of the Placenta / Douglas A Kniss, Teng Ma -- The Use of Ultrasound Contrast Agents in Placental Imaging / Jacques S Abramowicz -- Microscopy and the Placenta / William E Ackerman, Toshihiro Takizawa, John M Robinson -- Proteomics and the Placenta / Gregory E Rice -- Stable Isotope Methodologies for the Study of Transport and Metabolism In Vivo / Irene Cetin, Chiara Manḍ -- Medical Diseases and Complications. The Role of the Placenta in Autoimmune Disease and Early Pregnancy Loss / Daniel L Jackson, Danny J Schust -- The Placenta in Preterm Prelabor Rupture of Membranes and Preterm Labor / Chong Jai Kim, Roberto Romero, Sonia S Hassan -- Diabetes and the Placenta / Ursula Hiden, Julia Froehlich, Gernot Desoye -- Placental Origins of Intrauterine Growth Restriction / Ian P Crocker -- The Placenta in Preeclampsia / Fiona Lyall -- Thrombophilia and the Placenta / Christina S Han, Michael J Paidas -- Infections in the Placenta / Samuel Parry -- Aneuploidy and Polyploidy / Dan Diego-Alvarez, Wendy P Robinson -- Gestational Trophoblastic Disease and Placental Tumors / Katja Gwin, Aliya N Husain -- Multiple Gestation and Twin-Twin Transfusion Syndrome / Ramesha Papanna, Kenneth Moise -- Previa and Abruption / Helen H Kay -- The Placenta as a Functional Barrier to Fetal Drug Exposure / Tatiana N Nanovskaya, Gary D V Hankins, Mahmoud S Ahmed -- Placental Drug Transport / Clifford W Mason, Carl P Weiner -- Future Clinical Applications. Umbilical Cord Blood Banking / Gilad A Gross, Thinh Nguyen, Laura Meints -- Stem Cells from the Placenta / Thaddeus G Golos -- Fetal DNA, RNA, and Prenatal Diagnosis / Olav Lapaire, Wolfgang Holzgreve -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Placenta -- Diseases; Placenta; Placenta; Placenta Diseases; Placenta; Placenta -- Diseases; Electronic books